The Role of Green Infrastructure in Mitigating Urban Flooding - Jinto P J (International Journal of Applied and Scientific Research, 2024)
Urban flooding has emerged as a critical challenge due to rapid urbanization, climate change, and the loss of natural drainage systems. Traditional grey infrastructure, such as stormwater drains and concrete embankments, often fails to handle increasing rainfall intensity, leading to waterlogging and economic losses. Green infrastructure (GI) offers a sustainable approach by integrating natural and semi-natural systems to manage stormwater effectively. This paper examines the role of green infrastructure in mitigating urban flooding through mechanisms such as permeable surfaces, green roofs, wetlands, urban forests, and rain gardens. By enhancing water absorption, reducing runoff, and improving resilience to extreme weather events, GI provides a cost-effective and ecologically beneficial alternative to conventional flood control methods. The paper also explores global case studies of successful GI implementation and presents policy recommendations for cities aiming to integrate green infrastructure into urban planning